Ocular Sebaceous Carcinoma In Situ With Biphenotypic Differentiation: A Reappraisal of the Alternative Origin of the Tumor. (December 2020) - Yim, C. L.; Lam, S. C.; Yuen, Hunter Kwok Lai; Cheuk, Wah
Ocular sebaceous carcinoma is an uncommon, aggressive tumor arising from the Meibomian gland, Zeis gland, or sebaceous glands in the caruncle or eyelashes. We described a rare case of sebaceous carcinoma in situ in a 51-year-old female that was characterized by intraepithelial growth of sebaceous carcinoma cells with no invasive carcinoma in the underlying sebaceous glands. Early stromal invasion was identified that featured 2 distinctive but focally intermixed populations of sebaceous carcinoma cells and squamous carcinoma cells. The 2 populations of cells exhibited their respective distinct immunophenotype but both showed strong overexpression of p53. This case provides evidence to support the hypothesis that some ocular sebaceous carcinoma may arise from intraepithelial pluripotent stem cells.